2007
DOI: 10.1177/147323000703500512
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Plasma Fibrinogen Levels and the Clinical Features of Patients with Ovarian Carcinoma

Abstract: Pre-operative plasma levels of fibrinogen, plasma prothrombin time, activated partial thromboplastin time and thrombin time (TT) were retrospectively examined in 105 patients with ovarian carcinoma and 21 control patients with benign ovarian tumour. Plasma cancer antigen 125 (CA-125) levels, pathological type, age, body mass index and blood group were evaluated. The TTs of patients with stage III and stage IV ovarian carcinoma were significantly shorter than in controls. Levels of plasma fibrinogen in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…This was in accordance with previously published data on patients with other malignancies (810,24,28). …”
Section: Discussionsupporting
confidence: 93%
“…This was in accordance with previously published data on patients with other malignancies (810,24,28). …”
Section: Discussionsupporting
confidence: 93%
“…Elevated pretherapeutic plasma fibrinogen levels were associated with higher tumor stage. This is in accordance with previously published data in patients with other malignancies [16,17,20,21], reflecting the fact that the plasma fibrinogen level seems to rise with tumor growth, progression, and metastasis. This might be caused by direct activation of blood coagulation by the induction of thrombin through the activity of tumor cell procoagulation.…”
Section: Discussionsupporting
confidence: 93%
“…We found high plasma fibrinogen levels to be associated with tumors that were greater in number and larger in size; more advanced HCC, which is consistent with previous reports regarding other human cancers [7,1618] ; and an increased frequency of portal vein invasion, which may indicate that increased plasma fibrinogen levels are associated with increased tumor growth and progression. Second, our results demonstrated that patients with high plasma fibrinogen levels had lower rates of overall survival and tumor-free survival, and most importantly, patients with elevated plasma fibrinogen levels demonstrated poorer response to TACE.…”
Section: Discussionsupporting
confidence: 91%